Influence of melatonin and sexual hormones on the expression of proliferating cell nuclear antigen in the adrenal cortex of a seasonal breeder (Lagostomus maximus) - Gallol, Luis Ezequiel (2020)
The viscacha (Lagostomus maximus) is a rodent of nocturnal habits, whose physiology and behavior vary according to modifications of environmental signals. The objective of this study is to assess the influence of melatonin and sexual hormones on the viscacha adrenal cortex proliferative activity through the immunohistochemical detection of proliferating cell nuclear antigen (PCNA) along with hormonal determinations. PCNA expression was studied in male viscachas to assess the effect of melatonin administration, castration and the annual reproductive cycle. In female viscachas, PCNA was studied in nonpregnant and pregnant viscachas. PCNA expression was observed in adrenocortical cells (PCNA-A) and endothelial cells (PCNA-E). Melatonin-administered animals showed a significantly lower number of PCNA-A compared to the control group. No significant difference could be established in the number of PCNA-A and PCNA-E between castrated and control animals. However, the morphometric analysis showed an increase in the size of the cortex of castrated animals, along with other cytological features. Significant differences in serum testosterone levels were observed during the male viscacha reproductive cycle, with the lowest levels encountered during the regression period (winter). Male viscachas exhibited a significantly high number of PCNA-A during late autumn and a high number of PCNA-E during winter. In females, hormonal determinations showed a peak of progesterone and estrogen during mid-pregnancy, along with a notably high number of PCNA-A and an increase in the number of PCNA-E. Our results suggest that proliferation in the adrenal cortex of the viscacha varies in relation to melatonin, sexual hormones and environmental conditions.